Relationship between nutrition knowledge and nutritional adequacy in Japanese university students: a cross-sectional study - Yatsuki Yanagihara; Aiko Narumi-Hyakutake (Journal of Nutritional Science)
The aim of this study was to examine the relationship between nutrition knowledge and nutritional adequacy among Japanese university students. This cross-sectional study was conducted in 2018 at a university located in Hyogo Prefecture, Kobe, Japan, and 801 students from various academic disciplines were enrolled. Eligible participants were students aged more than 18 years, encompassing all years of study. Nutrition knowledge data were obtained using a nutrition knowledge questionnaire (NKQ) for Japanese adults. Participants were classified into three nutrition knowledge groups according to their total NKQ scores [mean ± standard deviation; all (64.7 ± 15.4%), low (48.1 ± 13.8%), medium (68.3 ± 2.8%), and high (78.5 ± 4.2%)]. Participants reported their dietary habits in the preceding month using a brief self-administered diet history questionnaire. Differences in nutritional adequacy among groups were determined using logistic regression and covariance analyses, adjusted for potential confounding factors. The adequacy of each nutrient was quantified as the proportion of participants with nutrient intake that fell outside the reference range. Although the intakes of only a few nutrients and foods were associated with nutrition knowledge, the total number of nutrients below the estimated average requirement was lower in the high nutrition knowledge group (3.1 ± 2.7) than in the low nutrition knowledge group (3.6 ± 2.9) (P = 0.046). In conclusion, the nutrition knowledge level of Japanese university students is associated with nutritional adequacy but may partially affect eating habits. Future longitudinal studies must clarify the causal and dose-response relationships between nutrition knowledge and dietary habits.